2023
DOI: 10.1088/1361-6463/acec81
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution characteristics of the excited species in a pulsed needle-water discharge: effect of voltage and frequency

Abstract: Transient spark discharge has a broad application prospect due to its excellent performance in generating reactive oxygen species, but there is currently limited research on the transient excited species which are the important precursors for the formation of these species. This paper obtained a transient spark discharge with a needle-water electrode configuration, and then developed an optical detection system based on photomultiplier to measure the temporal evolution of four excited species. It is observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…This discharge and the accompanying current signal last during most of the pulse, approximately 1.4 µs. A similar observation was also reported in [36] and [22]. Here we have to distinguish between the different behavior of positive and negative operation, i.e.…”
Section: Pulsed Dischargesupporting
confidence: 77%
See 1 more Smart Citation
“…This discharge and the accompanying current signal last during most of the pulse, approximately 1.4 µs. A similar observation was also reported in [36] and [22]. Here we have to distinguish between the different behavior of positive and negative operation, i.e.…”
Section: Pulsed Dischargesupporting
confidence: 77%
“…The large range of different aspects investigated on plasmawater interaction in other works [7,[14][15][16][17][18][19][20][21][22] demonstrates the complexity of this topic. Therefore, knowledge on the interdependency of plasma and water properties is of importance for a better understanding of underlying processes.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the temperatures during the two discharge phases are calculated in figure 9. The experimental spectrum of the SPS of N 2 captured in the streamer phase below a gate width of 5 ns is compared with the simulated spectrum in SPECAIR software to obtain the rotational temperature and vibrational temperature [36,37]. The experimental spectrum fits well with the simulated spectrum as shown in figure 9(a); thus, a rotational temperature of 500 K and a vibrational temperature of 2150 K during the streamer phase are obtained.…”
Section: Temperature and Electron Density Of The Dischargementioning
confidence: 75%
“…Thus, the cumulative thermal effect and positive feedback effect of thermal instability led to the rise in T g and ε . 56,57 Additionally, Guo et al reported that the memory effect of the residual charge in the discharge space would be enhanced with increasing frequency. 58 This also improved the total electric field which contributed to the rise in ε and T g .…”
Section: Resultsmentioning
confidence: 99%